Autism: Collaborative Perspektives in Education - Imanuel Hitipeuw (Universitas Negeri Malang, 2016)
Autism is the continuum of impairments. Children with autism show intellectual, social, emotional, and language or communication disorder. Collaboration is an important aspect in delivering education/intervention for children. Professionals have to have knowledge and skill related to autism and have to team up with parent in dealing with the disorder. The unique profile of the individual with autism calls for emphasis in the areas of communication skills, social-emotional, behavioral, and sensory regulation, and communication. Pre-identification of the children may help teachers and parents to make decisions whether the child needs a referral or not. In this case, Indonesia needs to make more political will in order to implement autism education in various setting to address immediate needs of the children before the problem becomes more complicated